The hidden geography of tourism firm spending: tracking economic leakages with firm-to-firm transactions - Stjepan Srhoj; Josip Mikulić (Global Labor Organization (GLO), 2025)
Tourism influences local economies through direct, indirect, and induced effects. Using novel firm-to-firm transaction data, we shed light on tourism's indirect effects. We find that tourism firms primarily source inputs locally or from the capital, with limited purchases from distant, poorer regions. While direct imports by tourism firms are relatively small, indirect imports-those embedded in supply chains-are substantial, comprising 54.2% of total supplier costs. Our findings suggest that overlooking indirect imports may lead to an overestimation of tourism's true economic contribution.
Keywords: L83; R12; F14; D22; O18; 330; firm-to-firm transaction data; economic leakages; supplier spending; indirect imports; local economic impact